Modifikasi Model Edukasi Meja Putar Sebagai Upaya Meningkatkan Tindakan Dalam Memelihara Kesehatan Gigi Pada Siswa - Yulyana Sendia Martina; Dwi Septiarini; Rohisotul Laily; Hayatunnufus (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Dental caries is a multifactorial disease that causes demineralization of the tough tissues of the teeth. One of the factors that contribute to tooth decay is poor behavior. 80% of the students in SD Yapita Surabaya School suffer from dental caries, with an average caries index reaching the